Fortified balanced energy-protein supplements increase nutrient adequacy without displacing food intake in pregnant women in rural Burkina Faso - de Kok, Brenda; Argaw, Alemayehu; Hanley-Cook, Giles; Toe, Laeticia Celine; Ouédraogo, Moctar; Diop, Loty; Becquey, Elodie; Huybregts, Lieven (Oxford University Press, 2021)
Background: In many low- and middle-income countries, the prevalence of energy and nutrient deficiencies is high among pregnant women. Balanced energy-protein (BEP) supplements are a promising strategy to cover nutritional requirements during pregnancy and improve birth outcomes. However, the displacement of nutrient-dense foods by BEP might attenuate the efficacy of supplementation. Objective: This cross-sectional study of participants in a randomized controlled trial evaluated the difference in energy and macro- and micronutrient intakes, food groups, and nutrient adequacy between a control and intervention group receiving either a daily iron–folic acid (IFA) tablet or IFA and BEP supplement during pregnancy, respectively. Methods: We collected a single multiple-pass 24-h recall from 470 pregnant women from the MIcronutriments pour la SAnté de la Mère et de l'Enfant (MISAME) III study that investigates the efficacy of BEP supplementation on birth outcomes and infant growth. Dietary intake (median and IQR) and nutrient adequacy were assessed using individual recipes and preparation methods of mixed dishes for each participant. Linear regression models were fitted to compare energy and nutrient intakes. Results: Dietary energy, and macro- and micronutrient intakes were significantly higher among women in the intervention group when including BEP [2329 kcal/d (1855, 3008 kcal/d) compared with 1942 kcal/d (1575, 2405 kcal/d) in the control group (all P < 0.001)]. The difference in median energy intake (448 kcal/d; 95% CI: 291, 605 kcal/d) was approximately equivalent to a daily dose of the BEP supplement (393 kcal). Nutrient adequacy ratios for both groups were low for all micronutrients (between 0.02 and 0.66), when excluding BEP (except iron and folic acid, due to standard supplemental doses) from analysis. However, nutrient intakes increased to the Estimated Average Requirement for pregnant women when including BEP supplements. Conclusions: BEP supplementation increases energy and macro- and micronutrient intakes among pregnant women and fills nutrient gaps without displacing food intake. This trial was registered at clinicaltrials.gov as NCT03533712 (https://clinicaltrials.gov/ct2/show/NCT03533712).